Mozart - Master of Clasical Music
Eine Klein Nachtmusik:Allegro/Piano concerto in A mojor,K488: Adagio/Flute Concerto in D major, K 314: Allegro/Symphony No.40 in G minor: Molto Allegro/ Clarinet Concert KV 622: Adagio/ Serenade, K 375: Menuetto.